Rapid Point-of-Care Testing for Detection of HIV and Clinical Monitoring. (23rd May 2013) - Arora, D. R.; Maheshwari, Megha; Arora, B.
Abstract : Reversing and arresting the epidemic of HIV are a challenge for any country. Early diagnosis and rapid initiation of treatment remain a key strategy in the control of HIV. Technological advances in the form of low-cost rapid point-of-care tests have completely transformed the diagnosis and management of HIV, especially in resource limited settings, where health infrastructure is poor and timely access to medical care is a challenge. Point-of-care devices have proven to be easy to transport, operate, and maintain, and also lower-skilled staff is equally able to perform these tests as compared to trained laboratory technicians. Point-of-care tests allow rapid detection of HIV allowing for rapid initiation of therapy, monitoring of antiretroviral therapy and drug toxicity, and detection of opportunistic infections and associated illnesses.